Combined effect of margosa oil and diflubenzuron on tobacco caterpillar (Spodoptera litura) and gram podborer (Helicoverpa armigera) - Durairaj, C; Venugopal, M S (The Indian Journal of Agricultural Sciences, 2012)
A laboratory experiment was conducted during 1992 to study the combined effect of margosa (Azadtrachta indica A. Juss.) oil and diflubenzuron in various combinations on tobacco caterpillar [Spodoptera Iitura (Fabr.)] and gram podborer [Helicoverpa armigera (HObn.)]. The insecticidal effect was assessed by their anti-feedant, morphogenetic effect and larval mortality. Margosa oil 2% + diflubenzuron 0.015% recorded the lowest leaf area (9.3 cm2) fed and faecal peUet weight (63 mg) with earlier larval mortality on tobacco caterpillar. In gram podborer the maximum anti-feedant activity with lowest faecal pellet weight (0.139 g) and earlier larval mortality (at 13 days after treatment) were recorded in margosa oil 2% + diflubellZllron 0.03 %. The larval mortality was due to difficulty in moulting between various stages of larval instars and the formation of larval-pupal mosaics.